Development of a High-Throughput Assay for Identifying Inhibitors of TBK1 and IKKε - Hutti, Jessica E.; Porter, Melissa A.; Cheely, Adam W.; Cantley, Lewis C.; Wang, Xiaodong; Kireev, Dmitri; Baldwin, Albert S.; Janzen, William P. (PLOS ONE, 2012)
IKKε and TBK1 are noncanonical IKK family members which regulate inflammatory signaling pathways and also play important roles in oncogenesis. However, few inhibitors of these kinases have been identified. While the substrate specificity of IKKε has recently been described, the substrate specificity of TBK1 is unknown, hindering the development of high-throughput screening technologies for inhibitor identification. Here, we describe the optimal substrate phosphorylation motif for TBK1, and show that it is identical to the phosphorylation motif previously described for IKKε. This information enabled the design of an optimal TBK1/IKKε substrate peptide amenable to high-throughput screening and we assayed a 6,006 compound library that included 4,727 kinase-focused compounds to discover in vitro inhibitors of TBK1 and IKKε. 227 compounds in this library inhibited TBK1 at a concentration of 10 µM, while 57 compounds inhibited IKKε. Together, these data describe a new high-throughput screening assay which will facilitate the discovery of small molecule TBK1/IKKε inhibitors possessing therapeutic potential for both inflammatory diseases and cancer.